(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
The purpose of this study is to present the changes in the upper small firms in the trade sector, in terms of communication, efficiency, management skills, identity, recognition and incentives and personal contribution, after the implementation of a management system in Lara State. Focused on the above analysis, pre-implantation and organizational aspects in postimplantation investigate the findings of the leaders responsible for the software features. I framed within a non-experimental, descriptive design transactional and aligned to a field study. The population was represented by 30 small companies higher, with occupation of 5-20 people and leaders through project managers, their opinions were collected by a data collection instrument. As for communication, project leaders indicated that improved communication system companies, for efficiency, there was an optimization, was observed in managerial skills, delegation of responsibility for maintenance of the system for identity changes minors, goals, objectives and policies of the organization and finally, personal contributions with the awards and incentives that were present but little importance.